A Paradox of Plenty? Rent Distribution and Political Stability in Oil States - Matthias Basedau; Wolfram Lacher (German Institute of Global and Area Studies (GIGA), 2006)
Resource curse theory claims that resource abundance encourages violent conflict. A study of 37 oil-producing developing countries, however, reveals that oil states with very high levels of oil revenue are remarkably stable. An analysis of the ways in which governments spend oil revenues identifies two distinct types of rentier systems - the large-scale distributive state and the patronage-based system - which are strongly linked to instability or its absence. However, some deviant cases, such as Equatorial Guinea and Gabon, illustrate the need for further research. Apparently, the notion of a 'paradox of plenty' has neglected rentier mechanisms that avoid conflict. – – Die Theorie des Ressourcenfluchs behauptet, dass Ressourcenreichtum gewaltsame Konflikte begünstigt. Eine Untersuchung von 37 ölproduzierenden Entwicklungsländern zeigt hingegen, dass Länder mit sehr hohen Ölerlösen bemerkenswert stabil sind. Die Analyse der Art und Weise wie Ölstaaten Ressourcenerlöse verwenden, führt zur Bildung zweier distinkter Typen von Rentierstaaten - dem Distributionstyp gegenüber dem Patronage-Typ -, die eine starke Korrelation mit politischer Instabilität oder deren Abwesenheit aufweisen. Einige abweichende Fälle, wie anhand der Fallstudien Äquatorial-Guinea und Gabun gezeigt werden kann, weisen aber auf die Notwendigkeit zukünftiger Forschung hin. Offenbar hat die Forschung zum 'Paradox of Plenty' und 'Ressourcenfluch' Rentiermechanismen vernachlässigt, die gewaltsame Konflikte verhindern können.
Keywords: N5; N50; O13; 330; Resource Curse; Paradox of Plenty; Oil; Rentier State; Violent Conflict; Political Stability; Developing World; Erdölvorkommen; Reichtum; Rent Seeking; Verteilungspolitik; Politische Unruhen; Schätzung; Welt; Entwicklungsländer; Politische Stabilität